Skill‐Biased Technological Change and Rising Wage Inequality: Some Problems and Puzzles - Card, David; DiNardo, John E. (Journal of Labor Economics, 2002)
The recent rise in wage inequality is usually attributed to skill-biased technical change (SBTC), associated with new computer technologies. We review the evidence for this hypothesis, focusing on the implications of SBTC for overall wage inequality and for changes in wage differentials between groups. A key problem for the SBTC hypothesis is that wage inequality stabilized in the 1990s despite continuing advances in computer technology; SBTC also fails to explain the evolution of other dimensions of wage inequality, including the gender and racial wage gaps and the age gradient in the return to education.